2016
DOI: 10.2341/15-079-t
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Veneers and Direct-Composite Cases of Amelogenesis Imperfecta Rehabilitation

Abstract: The aim of this article is to present two case reports for the treatment of patients affected with amelogenesis imperfecta. One case was treated with composite resin and the other case with ceramic veneers. Esthetic and functional results were achieved using both treatments, and a review of advantages and disadvantages is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…Shibata, Taguchi, Gondo, Stolf, and Baratieri () compared ceramic veneers and direct composite in AI rehabilitation. They concluded that the selection criteria for the two different materials used in rehabilitation of AI patients depends on (a) disorder type and severity, (b) patient age, (c) esthetic demand, (d) treatment longevity, (e) presence or absence of parafunctional habits, (f????????)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shibata, Taguchi, Gondo, Stolf, and Baratieri () compared ceramic veneers and direct composite in AI rehabilitation. They concluded that the selection criteria for the two different materials used in rehabilitation of AI patients depends on (a) disorder type and severity, (b) patient age, (c) esthetic demand, (d) treatment longevity, (e) presence or absence of parafunctional habits, (f????????)…”
Section: Discussionmentioning
confidence: 99%
“…Proper diagnosis and good treatment planning are fundamental to obtaining a satisfactory result for rehabilitation of patients with AI (Shibata et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are reports of failure in the resin adhered to enamel and/or dentine. Newer adhesive systems seem to correct these failures and thus it is necessary to choose the most adequate materials …”
Section: Discussionmentioning
confidence: 99%
“…This performance was based on the following parameters: marginal adaptation, secondary caries, and anatomy [22]. It should be noted that the repair of composite should be the treatment of choice when it is clinically indicated, since it is a minimally invasive treatment that can increase consistently longevity of the restoration [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The success of direct adhesive restorations depends directly on the formation and stability of an excellent hybrid layer [23].…”
Section: Discussionmentioning
confidence: 99%
“…Direct techniques using composite resins require the surgeon ability [5]. Some techniques are described using the diagnostic wax-up and silicone palatine guides to lead them to simulate the aesthetic of work and occlusal function pre-establishment during planning [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%